Identification of odor active substances in individual low-volume amniotic fluid samples by a sensorially targeted gas chromatographic-olfactometric approach. - Hartmann, Constanze; Cupisti, Susanne; Dittrich, Ralf; Büttner, Andrea (Chemosensory Perception, 2014)
The odor of amniotic fluid is repeatedly discussed with regard to its potential to provide olfactory cues to the unborn. However, the chemical basis for such assumptions is still unclear and the odorous composition of amniotic fluid, as well as inter-individual variances, has not yet been fully investigated. However, thorough examination of the odor and flavor profiles of the intra-uterine environment might support our understanding of early sensory triggers and potential sensory conditioning processes. Therefore, the aim of the present study was to characterize specific odorants in individual samples of amniotic fluid and to identify the most potent odor-active substances in this physiological fluid by means of gas chromatography olfactometry and aroma extract dilution analysis. The identification led to six new substances, which were not reported, to the best of our knowledge, for amniotic fluid before—among them the two steroids 5α-androst-16-en-3-one and 4, 16-androstadien-3-one.<br